The Taste and Tasting in Chinese Aesthetics - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2003)
The article deals with the meaning and functioning of the taste and tasting in Chinese aesthetics. Its influence on the development of the aesthetic terminology, the relationship with the other senses, the changes of its meaning in the history of Chinese aesthetics is investigated. It is argued that sense of the taste must not be ignored, as it often happens in the studies of Chinese aesthetics, in which the attention is paid to the visuality and hearing as the main aesthetic senses. The taste was not less important than that of the sight and hearing in Chinese aethetics, thus, only its investigation in the association with the other senses could be helpful in revealing the unique, that is synestetic nature of Chinese aesthetic worldview. The article starts with the brief overview of the etimology of the key concepts of Chinese aesthetics, such as li (ritual), he (harmony), mei (beauty) and their roots in the early (Shang-Zhou) ritual culture and its reflections, in which the food and its presentation was developed into the special kind of art. But the relation of the tasting of the food with the other senses (that of the colour, sound, smell) is not less important in the formation of the early Chinese aesthetic as well as ethic world view. Futher, the attention is drawn to the reflections of the taste in the association with the restrained taste (yiwei) and restrained sound (yiyin) in Confucian classics (“Liji”), as well as with the flavourlessness or insipidity (wuwei) in Daoist classics (“Laozi”). It is argued that those meanings had an ethical basis in Confucianism and ontological one in Daoism, giving the impetus for the further development of the main means of the aesthetic expression, namely, the suggestiviness in Chinese art. It was vitality (qi) which made possible to transform the early, more ordinary sense of taste into the subtle sense of flavour as the most important task for the artistic creativity and appreciation in Chinese aesthetics. It was transformed into the synthetic, non-verbal, sublime sense of the vitality of the cosmos and the mutual relationship of things, which is expressed in Chinese poetry, music and painting. Lastly, by the side with such suggestive flavour another kind of tasting, that of the woman’s bound feet existed, in which other senses are included as well, especially that of smell. Moreover, it reveals the same features of Chinese aesthetic worldview, namely, the inseparability of the nature and culture, and the transformatability (hila). The conclusion affirms that the taste and tasting can be treated as the means to reveal the coexistence of the “inner” and “outer” reality, which is the more important than the relationship of nature and culture in Chinese aesthetics.